Efektivitas Pembelajaran Aqidah Akhlak di Ponpes Raudlatul Wathani NW Taman Sari Desa Batu Nampar: The Effectiveness of Aqidah and Akhlak Learning at the Raudlatul Wathani Islamic Boarding School in NW Taman Sari, Batu Nampar Village - Tohri Ramdani (Al-Faiza : Journal of Islamic Education Studies, 2026)
In an Islamic school institution, Islamic religious education is a compulsory subject for students, one of which is the subject of aqidah and akhlak. The subject of aqidah and akhlak is a subject that studies the faith and morals of a Muslim in interacting with Allah and all of Allah's creatures in this world. The purpose of this study was to determine the factors that influence the effectiveness of aqidah and akhlak learning at the Raudlatul Wathoni NW Taman Sari Islamic Boarding School. Data collection techniques in this qualitative study can be obtained through participatory observation, interviews, and documentation. The steps for analysis are data collection, data reduction, data presentation, and drawing conclusions. The results of this study still require efforts to correct all existing deficiencies, so that existing problems can be resolved quickly, so that what is expected in the future can be realized. Therefore, to overcome all obstacles faced, it is the obligation of every principal and teacher to overcome them, because it is a way to improve education in schools and must be implemented properly.